Multiphysics mixed finite element method with Nitsche's technique for Stokes‐poroelasticity problem. Issue 1 (12th August 2022) - Ge, Zhihao; Pang, Jin'ge; Cao, Jiwei
Abstract: In this article, we propose a multiphysics mixed finite element method with Nitsche's technique for Stokes‐poroelasticity problem. Firstly, we reformulate the poroelasticity part of the original problem by introducing two pseudo‐pressures to into a "fluid–fluid" coupled problem so that we can use the classical stable finite element pairs to deal with this problem conveniently. Then, we prove the existence and uniqueness of weak solution of the reformulated problem. And we use Nitsche's technique to approximate the coupling condition at the interface to propose a loosely‐coupled time‐stepping method to solve three subproblems at each time step–a Stokes problem, a generalized Stokes problem and a mixed diffusion problem. And the proposed method does not require any restriction on the choice of the discrete approximation spaces on each side of the interface provided that appropriate quadrature methods are adopted. Also, we give the stability analysis and error estimates of the loosely‐coupled time‐stepping method. Finally, we give the numerical tests to show that the proposed numerical method has a good stability and no "locking" phenomenon.